Influencia del rol del gobierno local en la participación social de los adultos mayores usuarios del programa pensión 65 del distrito de Guadalupe, La Libertad, 2017. - Pizarro Tejada, Kassandra Patricia (2018)
The thesis research entitled "INFLUENCE OF THE ROLE OF THE LOCAL GOVERNMENT IN THE SOCIAL PARTICIPATION OF THE ELDERLY ADULTS USERS OF THE PENSION 65 PROGRAM OF THE DISTRICT OF GUADALUPE, LA LIBERTAD 2017", arises from the need to analyze the role played by local government in the face of the limited social participation of older adults, such as the institution responsible for ensuring the integral development of this vulnerable population and making the activities included in the policies of the protection to the elderly, which they have a duty to fulfill. In this research, the methods used were Inductive - deductive, ethnographic and statistical; the techniques used were observation, interview, survey and file review; Likewise, the instruments used were the observation register, interview records, questionnaire and documents. With the approach of this problematic reality, it is tried to analyze the role of the local government in front of this scenario, which needs an intervention that adjusts to it, since this population of older adults is in a state of vulnerability, with few possibilities of an active aging. Also, this research is intended to provide elements that can be taken into account by the authorities of the district and in this way, can start up activities according to the needs of older adults.